2002
DOI: 10.1103/physreve.65.032701
|View full text |Cite
|
Sign up to set email alerts
|

Elastic coupling of silica gel dynamics in a liquid-crystal–aerosil dispersion

Abstract: The dynamics of a thixotropic silica aerosil gel dispersed in an octylcyanobiphenyl liquid crystal were directly probed by x-ray intensity fluctuation spectroscopy. For all samples, the time-autocorrelation function of the gel was well described by a modified-exponential function over the q range studied. Compared to a pure gel sample, a dilute (0.06 g cm(-3)) gel embedded within the liquid crystal displayed more complex and temperature dependent dynamics. Near the second-order smectic-A-to-nematic phase trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
26
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 21 publications
2
26
0
Order By: Relevance
“…This would be consistent with large changes in the relaxation times of aerosil gels observed by dynamic x-ray studies on 8CB+aerosil near T IN [16]. In addition, this coupling should dampen director fluctuations and could account for the variation in the critical behavior seen at the N -SmA transition for LC+aerosil samples.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…This would be consistent with large changes in the relaxation times of aerosil gels observed by dynamic x-ray studies on 8CB+aerosil near T IN [16]. In addition, this coupling should dampen director fluctuations and could account for the variation in the critical behavior seen at the N -SmA transition for LC+aerosil samples.…”
Section: Discussionsupporting
confidence: 74%
“…x-ray scattering [14,15], x-ray intensity fluctuation spectroscopy [16], static and dynamic light-scattering [9,10,11], and deuterium NMR [17] studies on the nematic to smectic-A (N -SmA) and the isotropic to nematic (I -N ) phase transitions of this system have shown that there are clear quenched random-field characteristics as well as finite-size scaling effects…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, the scattering amplitude ratio as a function of ξ yields a 2 /σ 1 ∼ξ −2.68±0. 26 at ∆T = −6 K. The scatter in the experimental values of a 2 (∆T ) as a function of ρ S only allows a very rough estimate of its scaling, but it appears to be very weakly dependent on either correlation length or silica density. Unfortunately, the uncertainties in σ LT 1 values arising from fitting the x-rays profiles at low temperatures (where the quenched random term greatly overshadows the thermal fluctuation term) and the added uncertainties from normalization make it unsuitable for testing as a function of ρ S .…”
Section: Discussionmentioning
confidence: 93%
“…For 8CB+aerosils, an increase in ρ S appears to have the same effect. Recent work has found that aerosil gels exhibit dynamics which can couple to a host liquid crystal [26] presumably through direct coupling to director fluctuations. Also, recent deuterium NMR studies of 8CB+aerosils [6] found no appreciable change in the magnitude of orientational order above T * for ρ S < 0.1.…”
Section: Discussionmentioning
confidence: 99%
“…However few studies have been reported on FLCs under the influence of aerosil particles on isotropic-nematic, nematics-smectic A, and smectic A-smectic C * phase transition. [11][12][13][14] In this series, the enhanced electro-optical properties of gold NPs ͑GNPs͒ doped FLCs material have been studied where the interaction of GNPs with LC molecules was taken into account. 15 The memory effect in filled nematics ͑nano-particles or aerosils doped nematics͒ and NPs doped FLCs have been studied well.…”
mentioning
confidence: 99%